2003
DOI: 10.2139/ssrn.389060
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Entrepreneurship: Ethnic and Female Roles in Urban Economic Life

Abstract: The aim of this paper is to investigate the phenomenon of ethnic female entrepreneurship in urban economie life. The focus of the research is on the attitudes and behaviour of Turkish female entrepreneurs in Amsterdam. The main question we pose is: Are ethnic jèmale entrepreneurs special ethnic entrepreneurs or special female entrepreneurs? This paper provides an answer to this question on the basis of field surveys. The results of the case study research on Turkish female entrepreneurs in Amsterdam show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 32 publications
0
42
0
Order By: Relevance
“…(see Baycan-Levent et al, 2003Jones and Ram, 2007;Rath, 2000;Stiles and Galbraith, 2004;Waldinger et al, 1990;Ward and Jenkins, 1984). A wealth of scientific contributions and reviews on ethnic entrepreneurship can be found in Dana (2007).…”
Section: Self-employed Migrants Are Increasingly Resorting To What Ismentioning
confidence: 99%
“…(see Baycan-Levent et al, 2003Jones and Ram, 2007;Rath, 2000;Stiles and Galbraith, 2004;Waldinger et al, 1990;Ward and Jenkins, 1984). A wealth of scientific contributions and reviews on ethnic entrepreneurship can be found in Dana (2007).…”
Section: Self-employed Migrants Are Increasingly Resorting To What Ismentioning
confidence: 99%
“…In the literature, the idea of being one's own boss to obtain independence is often cited as an important motivation for becoming self-employed, in particular by male entrepreneurs (Baycan-Levent, Masurel, & Nijkamp, 2003;Brettell & Alstatt, 2007;Zarrugh, 2007). In another study (Hilbrecht & Lero, 2014) moreover, most participants identified independence as a significant motivational factor for business start-up, and several of the self-employed participants discussed experiencing a 'temporal flexibility' allowing them to organise their days in a way that permitted them to meet different needs in the family as well as in the business (for further elaboration of this theme, see Hilbrecht & Lero, 2014, p. 31).…”
Section: C) Entrepreneurship As a Preferred Choice For Participants Wmentioning
confidence: 99%
“…Since immigration (legal and illegal) has picked up in an expanded Europe, the involvement of immigrants in this process has become particularly visible (Baycan-Levent et al, 2003 and2006;Chaganti and Green, 2002;van Delft et al, 2000;Fairlie, 2004 andMasurel et al, 2002;and Zhou, 2004). An almost identical process has taken place in South Africa over the past fifteen years.…”
Section: Introductionmentioning
confidence: 99%